Excavations at Portchester Castle Volume III: Medieval, the Outer Bailey and its Defences - Cunliffe, Barry (Reports of the Research Committee of the Society of Antiquaries of London, 1977)
This is an account of excavations at Portchester Castle which took place under Barry Cunliffe in 1961-72. The volume deals with alterations made to the Roman fort between 1066 and 1632, when a castle was constructed in its interior. This volume describes the excavation programme and the evidence recovered for the structures of the outer bailey and its defences. Included are specialist reports on the building materials, and other material recovered, including pottery, small objects, and animal bones.